Performance pay and productivity: The moderating role of a high-wage policy - Uwe Jirjahn (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2015)
Using panel data from German establishments, this study finds that performance pay is associated with increased productivity only when it is coupled with a high-wage policy. This holds for individual-based performance pay, group-based performance pay and profit sharing.
Keywords: D20; J33; M52; 330; performance pay; high-wage policy; productivity; fixed effects regressions